Environmental & architectural phenomenology. Vol. 8, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 1997)
Vol. 8, No. 1, Winter 1997 (includes “items of interest,” "citations received,” book reviews of Robert Mugerauer's Interpretations on Behalf of Place & two books on sustainable design, and essays by Tammeron Francis & David Woolf).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals